Construção dinâmica de um sistema interactivo para visualização do código intermédio do processo de compilação - Matos, Paulo (2003)
O DOLPHIN is a framework conceived to help the development of high-performance, multi-language and multi-architecture compilers. It includes several components, one of them is designated by DOLPHIN – Front-End for the Web. This one is responsible for all DOLPHIN items related with the web, namely an integrated development environment that allows, between other things, to observe and analyze, as hiper-text, the information along the compilation process. In this article is introduced a new solution developed with this intent (visualize and analyze the information of the compilation process), with an interactive graphical interface, built dynamically from a description of the information done at XML.